Establishment of Hysteresis Stiffness Model and Kinematic Precision Analysis of Manipulators - He Junkai; Yue Xiaoli; Li Yuliang; Ma Feihong (Jixie chuandong)
Considering the hysteresis effect of the harmonic reducer in the joint and that when the joint is subject to alternating load torques, the hysteresis effect will have great influence on the output precision. However, the load on each joint of the multi-DOF manipulator is not constant and the hysteresis effect of harmonic reducers in the joint should be considered when analyzing the precision of the manipulator's end motion. A stiffness model with the hysteresis effect is proposed. Combined with the Stribeck friction model, a dynamic model of the manipulator is established. By solving the model, the end motion trajectory of the manipulator considering the hysteresis of the harmonic reducer's torsional angle is obtained. The motion accuracy index is established and the influence of the hysteresis angle and torsional stiffness of harmonic reducers on the trajectory accuracy of manipulators is analyzed. The results can provide reference for the harmonic reducer in the engineering design process of manipulators.